Certain Classes of Operators on Some Weighted Hyperbolic Function Spaces - A. El-Sayed Ahmed; Amnah E. Shammaky (Journal of Mathematics)
In this paper, some classes of concerned multiplication operators consisting of analytic and hyperbolic functions are defined and considered. Furthermore, some properties such as boundedness and compactness of the new operators are discussed. Finally, a general class of weighted hyperbolic Bloch functions is characterized by metric spaces.